Seasonal environmental variability drives the swimming performance of a resident Iberian fish - Silva, S.S. (2021)
Swimming performance is a determinant characteristic for the survival of fish species and is related to their response to environmental disturbance. In this study, we evaluated how seasonal environmental variability of Mediterranean intermittent rivers influences swimming performance of a resident Iberian fish, the ruivaco, Achondrostoma oligolepis. Approximately forty fish of A. oligolepis were captured in each annual season (i.e. winter, spring, summer and autumn), from a Portuguese intermittent river, and compared in terms of swimming behaviour and capacity (Ucrit test). We found a clear distinction in fish willingness to swim and swimming performance between seasons. Fish were more willing to swim during autumn and winter, as opposed to less energetic behaviour during spring and summer. Higher Ucrit values were observed during autumn (0.42 ± 0.17 m/s) and winter (0.48 ± 0.25 m/s), which in the studied river are typically characterised by high flows, strongly influenced by rainfall patterns. Results from this study contribute to increase the knowledge on movement dynamics of small, typically known as resident, fish species and how this relates to natural and seasonal environmental variability.